2018
DOI: 10.14710/rotasi.20.1.29-32
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Evaporative Cooling untuk Meningkatkan Kenyamanan Ruang

Abstract: Sistem pendingin Air Cooler atau evaporative cooling (EC) mempunyai keunggulan hemat energy  dan kontruksi sederhana. Namun kelemahannya adalah terjadi peningkatan kelembaban udara, sehingga hanya cocok digunakan pada daerah yang kelembaban rendah dan temperatur tinggi. Untuk wilayah Indonesia yang terdiri dua musin , hujan dan kemarau,  penggunaan unit pendingin  ini hanya cocok pada bulan kemarau, karena temperatur tinggi (hingga 34 C) dan kelembaban cukup rendah (RH 50 %). Mengingat kelemahan Air Cooler yai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…Some explored the materials used for the cooling pad (Suryana et al, 2014;Susila et al, 2019). Some investigated its application to buildings (Kindangen et al, 2015;Kindangen & Umboh, 2017;Mohammad et al, 2013;Seputra, 2018;Yunianto, 2018). The studies that focus on exploring cooling pad materials found that different properties of the cooling pad, i.e., materials, area, and thickness, could result in different performances (Suryana et al, 2014;Susila et al, 2019).…”
Section: Direct Evaporative Cooling For Buildingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some explored the materials used for the cooling pad (Suryana et al, 2014;Susila et al, 2019). Some investigated its application to buildings (Kindangen et al, 2015;Kindangen & Umboh, 2017;Mohammad et al, 2013;Seputra, 2018;Yunianto, 2018). The studies that focus on exploring cooling pad materials found that different properties of the cooling pad, i.e., materials, area, and thickness, could result in different performances (Suryana et al, 2014;Susila et al, 2019).…”
Section: Direct Evaporative Cooling For Buildingmentioning
confidence: 99%
“…In this regard, previous studies recommend the use of other complementary techniques. The most basic proposal combines DEC with natural ventilation (Yunianto, 2018). This recommendation can improve comfort and is relatively affordable.…”
Section: Direct Evaporative Cooling For Buildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the natural ventilation mentioned above, direct evaporative cooling (DEC) can also be an alternative for cooling a building in a warmhumid climate like Surabaya. However, the utilization of DEC in warm-humid areas is limited (Mohammad et al 2013;Yunianto 2018). This limitation owes that the use of the technique can increase internal air humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the method can help reduce air temperature considerably, the increase in relative humidity can restrict the evaporation process in the human body and thus elevates discomfort (Poku, W. Oyinki, and A. Ogbonnaya 2017;Rao and Datta 2018). Nevertheless, several studies recommend the use of the technique if it is coupled with other strategies that can help to minimize the increase in air humidity (Yunianto 2018;Suwannapruk, Prieto, and Janssen 2020;Raza et al 2020;Hussain et al 2020;Chang et al 2020;Alwetaishi et al 2020;Suryo et al 2000;Sajjad et al 2021). If the increased air humidity is not too high, it can be compensated by sufficient air velocity in internal space.…”
Section: Introductionmentioning
confidence: 99%